Targeted next-generation sequencing in chronic lymphocytic leukemia: a high-throughput yet tailored approach will facilitate implementation in a clinical setting - Sutton, Lesley-Ann; Ljungström, Viktor; Mansouri, Larry; Young, Emma; Cortese, Diego; Navrkalova, Veronika; Malcikova, Jitka; Muggen, Alice F; Trbusek, Martin; Panagiotidis, Panagiotis; Davi, Frederic; Belessi, Chrysoula; et al. (Haematologica, 2015)
Next-generation sequencing has revealed novel recurrent mutations in chronic lymphocytic leukemia, particularly in patients with aggressive disease. Here, we explored targeted re-sequencing as a novel strategy to assess the mutation status of genes with prognostic potential. To this end, we utilized HaloPlex targeted enrichment technology and designed a panel including nine genes: ATM, BIRC3, MYD88, NOTCH1, SF3B1 and TP53, which have been linked to the prognosis of chronic lymphocytic leukemia, and KLHL6, POT1 and XPO1, which are less characterized but were found to be recurrently mutated in various sequencing studies. A total of 188 chronic lymphocytic leukemia patients with poor prognostic features (unmutated IGHV, n=137; IGHV3-21 subset #2, n=51) were sequenced on the HiSeq 2000 and data were analyzed using well-established bioinformatics tools. Using a conservative cutoff of 10% for the mutant allele, we found that 114/180 (63%) patients carried at least one mutation, with mutations in ATM, BIRC3, NOTCH1, SF3B1 and TP53 accounting for 149/177 (84%) of all mutations. We selected 155 mutations for Sanger validation (variant allele frequency, 10-99%) and 93% (144/155) of mutations were confirmed; notably, all 11 discordant variants had a variant allele frequency between 11-27%, hence at the detection limit of conventional Sanger sequencing. Technical precision was assessed by repeating the entire HaloPlex procedure for 63 patients; concordance was found for 77/82 (94%) mutations. In summary, this study demonstrates that targeted next-generation sequencing is an accurate and reproducible technique potentially suitable for routine screening, eventually as a stand-alone test without the need for confirmation by Sanger sequencing.
Keywords: nádorové proteiny; exprese genu; Gene Expression; Gene Frequency; mutace; High-Throughput Nucleotide Sequencing; prognóza; sestřihové faktory; RNA Splicing Factors; receptor Notch1; fosfoproteiny; Receptor, Notch1; nádorový supresorový protein p53; Phosphoproteins; frekvence genu; Leukemia, Lymphocytic, Chronic, B-Cell; lidé; Humans; vysoce účinné nukleotidové sekvenování; Neoplasm Proteins; Prognosis; malý jaderný ribonukleoprotein U2; Ribonucleoprotein, U2 Small Nuclear; Mutation; myeloidní diferenciační faktor 88; Alleles; Myeloid Differentiation Factor 88; alely; chronická lymfatická leukemie; Tumor Suppressor Protein p53